Owner Practices and Customer Perceptions in Sustainability and Social Media Marketing for Café SMEs - Safitri, Dhira Ervina; Nursaid,; Santoso, Budi (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Small and medium enterprises (SMEs), especially in the café industry, face challenges in meeting customer expectations for sustainability and digital engagement. The gap between owner practices and customer perceptions often leads to suboptimal business performance.Purpose: This study investigates the influence of sustainability marketing and social media marketing on the business performance of café SMEs in Jember, Indonesia, by integrating owner strategies and customer perceptions.Design/methodology/approach: Using an Exploratory Sequential Mixed Methods design, the study conducted qualitative interviews with 10 café owners in mid-May 2025 to explore sustainability and digital marketing practices, followed by a quantitative survey of 215 café customers conducted from May to June 2025 to validate and measure the constructs. Data was analyzed using Structural Equation Modeling (SEM) with SmartPLS v.4.0, including validity and reliability tests.Findings/Result: The study found that sustainability marketing and social media marketing significantly influence café SMEs’ business performance. Social media marketing showed a stronger direct effect (β = 0.638, p < 0.001) compared to sustainability marketing (β = 0.140, p = 0.027). Moreover, social media marketing mediates the relationship between sustainability marketing and performance (β = 0.410, p < 0.001), emphasizing its strategic role in transforming sustainability initiatives into measurable business value. Qualitative findings confirmed that café owners use Instagram and TikTok to promote local sourcing, eco-friendly campaigns, and customer engagement, turning sustainability narratives into digital competitiveness and long-term growth.Conclusion: This study demonstrates that integrating sustainability marketing with social media strategies significantly enhances the performance and competitiveness of café SMEs. Social media serves as a vital bridge that transforms sustainability initiatives into customer engagement, brand loyalty, and measurable business growth.Originality/value (State of the art): This research highlights the growing significance of digital entrepreneurship in the Cafe sector, offering insights into how various digital strategies influence consumer purchasing behavior, which is crucial for adapting to the evolving market landscape.Keywords:   business performance, exploratory sequential, smes performance, social media marketing, sustainability marketing